Water-in-Oil Microemulsions for Protein Delivery: Loading Optimization and Stability - R. Perinelli, Diego; Cespi, Marco; Pucciarelli, Stefania; Vincenzetti, Silvia; Casettari, Luca; K.W. Lam, Jenny; Logrippo, Serena; Canala, Elisa; E. Soliman, Mahmoud; Bonacucina, Giulia; F. Palmieri, Giovanni (Current Pharmaceutical Biotechnology, 2017)
Background: Microemulsions are attractive delivery systems for therapeutic proteins and peptides due to their ability to enhance bioavailability. Although different proteins and peptides have been successfully delivered through such ternary systems, no information can be found about protein loading and the formulation stability when such microemulsions are prepared with pharmaceuticallyapproved oils and surfactants. The aim of this work was to optimise a ternary system consisting of water/ ethyl oleate/Span® 80-Tween® 80 and to determine its protein loading capacity and stability, using bovine serum albumin (BSA) as a model of biomolecule. Methods: The optimization was carried out using a Central Composite Design and all the prepared formulations were characterised through dynamic light scattering, rheology, optical and polarized microscopy. Subsequently, the maximum loading capacity was determined and the stability of the final microemulsion with the highest content of protein was followed over six months. To investigate the structural features of the protein, BSA was recovered from the microemulsion and analysed through fluorescence spectroscopy. Results: After incorporation of the protein in the microemulsion, a decrease of its aqueous solubility was observed. However, the formulation remained stable over six months and the native-like state of the recovered protein was demonstrated by fluorescence spectroscopy Conclusion: This study demonstrated the feasibility of preparing microemulsions with the highest content of protein and their long-term stability.
Keywords: protein loading